2010
DOI: 10.3171/2010.4.spine09591
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal endoscopy to enhance the diagnosis of tethered cord syndrome

Abstract: Currently, endoscopic identification of the posteriorly displaced filum, which was confirmed at open surgery, is the essential diagnostic study for TCS or the tethered spinal cord. Furthermore, the stretch test of the filum proves its inelasticity, and filum sectioning leads to ascension and relaxation of the caudal spinal cord. These results can be linked to the impaired oxidative metabolism of the lumbosacral cord under excessive tension and to the metabolic and neurological improvements seen after filum sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Other studies have shown that endoscopic visualization of the intrathecal contents and the filum terminale is possible in cadaver specimens (8,9) and in clinical patients (10,11). These studies utilize small endoscopic cameras that do not contain a working channel.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that endoscopic visualization of the intrathecal contents and the filum terminale is possible in cadaver specimens (8,9) and in clinical patients (10,11). These studies utilize small endoscopic cameras that do not contain a working channel.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, in contrast to our technique, flexible systems could not go beyond the visualization of the lumbar intradural space. 26 Furthermore, laminectomy or sacral hiatus were the only way to reach the dura mater. There was also no verification of filum terminale specimens with histopathologic examination in previous autopsy series that proved the efficacy of minimally invasive surgery in reaching the filum terminale.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis and/or treatment of tethered cord syndrome, arachnoiditis, and spinal subdural hematoma can be established. [23][24][25][26] A novel endoscopic technique for the visualization and surgical manipulation of the filum terminale with no assistance from a loupe or microscope was described and supported with Key words -Filum terminale -Interlaminar -Minimal invasive spine surgery -Spinal endoscopy -Tethered cord syndrome -Untethering histopathologic examination. The utility, safety, and feasibility of this method were investigated in fresh postmortem adult human cadavers.…”
Section: Introductionmentioning
confidence: 99%
“…Karakhan et al 14 described different approaches, including a dorsal paramedian approach to the intradural space via interlaminar fenestration or hemilaminectomy. Woods et al 30 used the same type of endoscope as we did in the study presented here, and performed endoscopy to diagnose tethered cord syndrome prior to wide exposure of the dura.…”
Section: Discussionmentioning
confidence: 99%